İstanbullu Logolar - Küçükerdoğan, Rengin (İstanbul Kültür Üniversitesi Yayınları, 2007)
Ferdinand de Saussure'e göre değeri oluşturulan ilkeler, "değeri belirlenecek şeyle değiştirilebilir benzemez bir öğe ve değeri söz konusu olan şeyle karşılaştırılabilir benzer öğeler"dir. Buna dayanarak, değerin var olabilmesi bu ilkeye bağlıdır. Bu bağlamda logo oluştucularının arasındaki karşıtlıklar, logoların birbirlerinden farklılaşmasına böylelikle değer kazanmasına olanak tanır. Kurumlar birbirinden görsel iletişim çerçevesinde logolarıyla ayrılmaktadır. Yalın bir anlatımla değerin yaratımında logo tasarım öğelerinin ve bu öğelerin birbirleriyle ilişkilerinin önemi anlamlandırma ve farklılaşma bakımından çok büyüktür. Renk, biçim, çizgi, amblem ve tipografi, logonun dokusunu oluşturmaktadır. Logolar ise İstanbul'un kurumlarıyla oluşturduğu dokusunu görsel biçimde bizlere aktarmaktadırlar. Bu çerçevede hazırlanan çalışmada seçmeci göstergebilimsel yöntem aracılığıyla İstanbullu Logolar çözümlenmektedir.

According to Ferdinand Saussure, the principles determining value are both a non-similar element that can be altered with the thing whose value would be under concern. Regarding this, we can say that the presence of value is dependant upon these two principles. In this context, the possible contradictions among the logo-designers give birth to the differentiation in logos by permitting them to gain value. Institutions, within the context of visual communication, differentiate fromeach other trough logos. Plainly, troughout the process of value creation, the importance of logo designing elements and the relationship between these elements is greater with regard to the procedures of meaning and differentiation. Color, form, line, amblem and thpography are the elements determining the general texture of logo. Logos represent Istanbul's general texture formed mainly by its instituitions to us visually. In this regard, it can be declared that this paper is aimed to make the selective semiological analysis of İtanbullian logos possible.
Keywords: Görsel Gösterge; Değer; Tasarım; Logo; Çözümleme; Visual Indicators; Value; Design; Analysis